Macrobending Multimode Plastic Optical Fiber Coated with PANI-PVA composite as a pH sensor - Rohedi, Ali Yunus; Ainun, Rizqi Nur; Fatimah, Iim; Puspitasari, Nurrisma; Sudarsono, S; Yudoyono, Gatut (Jurnal Fisika dan Aplikasinya, 2024)
The measurement of pH is very important in the medical, industrial and research worlds and each requires measuring instruments with different sensitivities.Measuring the pH of a solution in principle measures hydrogen ions in a solution.In this research, a pH sensor was designed and fabricated using multimode fiber optic macrobending with the fiber optic cladding being peeled off and replaced with a PAni-PVA (polyaniline-polyvinyl alcohol) composite layer.The bending diameter of plastic fiber optics is varied with sizes d = 2.5 cm, d = 2 cm, and d = 1.5 cm.The test results show that the pH sensor created is capable of measuring the pH of the solution linearly in the range pH = 2 to 10 <w:LsdException Locked="false" Pri